(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It describes an approach to scientific education, developed and experienced in the training of teachers and researchers, in a graduate course in applied linguistic studies, in the Northern Region of Brazil. In this sense, this article presents the characterization of a tool called Science Education Circuit (SEC), used in course planning from the perspective of the mentioned approach. Documentary research also illustrates the challenges established in a task of scientific dissemination that is part ofplanning. It is based on an ant disciplined articulation of theoretical assumptions about research practices in teaching and teacher training. The study showed that the procedural facet of scientific education was favoredby the collaborative planning of the course, and it revealed four linguistic activities introduced in the rewriting of opinion articles produced and published in newspapers: lexical choice; defined nomenclatures; reference and citation; and focused content. This task guaranteed an experience of scientific dissemination by graduate students.